(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
World Health Organization (WHO) the mother organisation of all global health initiativesis actively involved in conceiving effective strategies to fight different Communicable and Non- Communicable Diseases (NCDs) worldwide. WHO has the goal to serve poorer nation effectively so that they can have fair access to various vaccines and drugs.The organisation is also ensuring sustainable financing for the global health sector. However, to deliver the effective health initiatives all across the continents, WHO should reason more efficiently with the regional offices so that it can collaborate in decision making and implement those decisions more precisely and decisively. WHO should act in coordination with other private, country-based and global organisations. It should advocate for research independent of any industrial interest, human rights policies and improvement of health services. WHO needs to modify its global endeavours which will intensify international responses in combating any emergency.To hold on to its current leadership role, if necessary, WHO should undergo significant reformation. Until present days, there is no substitute for WHO. WHO should realise that without empowering the marginalised people no global health goal can be achieved adequately. JCMCTA 2016 ; 27 (2) : 4 - 8